Adaptabilitas Karier Mahasiswa PPG Prajabatan di Universitas Syiah Kuala - Amna, Dinatil; Nurbaity, Nurbaity; Rahmiyati, Evi (Program Studi Bimbingan dan Konseling, FKIP, Universitas Syiah Kuala, 2023)
This research aims to determine the description of the Career Adaptability of Pre-Service Teacher Professional Education (PPG) Students at Syiah Kuala University. The sampling technique in this research is the Probability sampling technique, namely a sampling technique that provides equal opportunities for each member of the population. The sample in this study was 134 Pre-Service PPG students at Syiah Kuala University. The results of the frequency distribution show that less than half of the career adaptability of Pre-Service PPG students is at a very high level (45%) and high (45%), while a small percentage is at a medium level (6%) low (4%) and very low (1 %). This indicates that the majority of students have a very high level of career adaptability. Students' career adaptability categorization tends to have an awareness of the importance of career selection, career planning, and career development. They also tend to take responsibility for their decisions and actions regarding their career. However, some students still have challenges related to self-confidence and ability to do assignments efficiently. The results of this research show that the career adaptability of Pre-Service PPG students at Syiah Kuala University is relatively high, which is inversely proportional to the problem background which refers to students still experiencing difficulties in adapting to their new environment. Pre-service PPG students at Syiah Kuala University show a fairly good level of career adaptability, although there are still several areas where they can improve their abilities, such as increasing self-confidence and efficiency at work.